2018
DOI: 10.26603/ijspt20180493
|View full text |Cite
|
Sign up to set email alerts
|

Pitching Mechanics in Female Youth Fastpitch Softball

Abstract: Background: Fastpitch softball is a popular sport for young females. However, data are limited describing youth pitching mechanics. Normative data describing pitching mechanics in the two youngest player pitch leagues are critical to gaining an improved understanding of proper mechanics in an attempt to establish injury prevention programs. Purpose: The purpose of this study was to examine pitching mechanics in Little League softball pitchers and examine the relationship of these mechanics and participant anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 20 publications
2
52
3
Order By: Relevance
“…Thus, when examining the influence of glove arm positioning and shoulder kinetics, an active glove arm, as defined by keeping the glove arm in line with the target throughout all phases of the pitching motion, helps generate an energy efficient motion. Because the sport of softball has increased overuse injuries seen by clinicians [9,26,28,33], limiting the accumulated stress seen at the shoulder of a windmill softball pitcher should be of interest to the clinician. By minimizing joint loads of the pitching shoulder, an active glove arm will aid in the health and longevity of a pitcher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when examining the influence of glove arm positioning and shoulder kinetics, an active glove arm, as defined by keeping the glove arm in line with the target throughout all phases of the pitching motion, helps generate an energy efficient motion. Because the sport of softball has increased overuse injuries seen by clinicians [9,26,28,33], limiting the accumulated stress seen at the shoulder of a windmill softball pitcher should be of interest to the clinician. By minimizing joint loads of the pitching shoulder, an active glove arm will aid in the health and longevity of a pitcher.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still much to learn about the biomechanics of the windmill softball pitch and injuries. Though there are studies that have examined pitching mechanics in softball [6,8,26,27,31,37,38], there remains a deficiency in understanding the mechanical efficiency of the pitch and injury prevention. Softball pitching is a total body dynamic activity; therefore, the mechanics of the entire system, including the motion of the glove arm in addition to the pitching arm, warrant examination.…”
Section: Introductionmentioning
confidence: 99%
“…This finding leads us to believe that an over-exaggerated stride length may be problematic in maintaining balance and thus affects energy transfer up the kinetic chain and into the upper extremity. However, stride length has also revealed a direct positive relationship with ball velocity in softball pitching [16,17,21]; therefore, we hypothesize there may be a tipping point at which a longer stride length may have negative impacts on not only injury susceptibility but also pitch performance.…”
Section: Effects Of a Simulated Game On Pitching Kinematics In Youth mentioning
confidence: 83%
“…stability that facilitates the generation of high angular velocities in the joints of the upper extremity [19,20]. Therefore, pathomechanics associated with trunk positioning could have major implications not only for performance but also for injury susceptibility [15][16][17][18][19][20]. Research of elite softball pitchers has suggested that those who display a greater degree of trunk rotation at foot contact and a lesser degree of trunk lateral flexion at ball release were more likely to experience upper extremity pain [3,14].…”
Section: Effects Of a Simulated Game On Pitching Kinematics In Youth mentioning
confidence: 99%
See 1 more Smart Citation